Advanced Rectal Adenocarcinoma Presenting with Chronic Gastrointestinal Symptoms: A Case Report Highlighting the Role of Multidisciplinary Management and MRI Staging - Das, Sarthak; Sahu, Priyansh; Shrivastav, Aditya; Thitame, Sunil (Indian Journal of Case Reports, 2025)
Rectal adenocarcinoma, a prevalent form of colorectal cancer, often manifests with subtle and progressive symptoms such as rectal bleeding, altered bowel habits, fatigue, and unintended weight loss. This case describes a 62-year-old male who presented with an eight-month history of gastrointestinal complaints including loose stools, rectal bleeding, anorexia, and significant fatigue. Imaging studies, including contrast-enhanced MRI, revealed a large ulcerative mass involving the rectum and extending to the rectosigmoid junction. Colonoscopy confirmed the presence of a friable, proliferative growth, and histopathological evaluation identified a well-differentiated adenocarcinoma. The patient underwent staging laparoscopy and a palliative loop colostomy, followed by a stable postoperative course. This case underscores the critical role of early diagnostic evaluation in patients with persistent lower gastrointestinal symptoms. Prompt identification and a coordinated multidisciplinary approach are essential for managing advanced rectal cancers and improving patient outcomes.